2018
DOI: 10.1186/s13046-018-0713-7
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TIM3 relieves immunosuppression through reducing regulatory T cells in head and neck cancer

Abstract: BackgroundT-cell immunoglobulin mucin 3 (TIM3) is a negative immune checkpoint and plays a crucial part in tumor-induced immune suppression. However, the mechanism of TIM3 in regulating immunosuppression in head and neck squamous cell carcinoma (HNSCC) was still not quite clear.MethodsWe carried out the immunohistochemistry staining of HNSCC tissue microarrays. Through quantification of the histoscore, we performed the correlation analysis among the TIM3, Galectin-9, Foxp3, CD68 and CD163. The effects of TIM3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 41 publications
2
76
0
Order By: Relevance
“…Accumulating evidences from in vivo studies have shown that TIM-3 blockade enhances anti-tumor immunity and suppresses tumor growth [11,31]. Therefore, TIM-3 could be considered as a potential candidate for IC inhibition due to the remarkable success of other IC inhibitors in treating various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences from in vivo studies have shown that TIM-3 blockade enhances anti-tumor immunity and suppresses tumor growth [11,31]. Therefore, TIM-3 could be considered as a potential candidate for IC inhibition due to the remarkable success of other IC inhibitors in treating various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in tumor growth and in Treg and CTLA-4 levels was observed following TIM-3 blockade, while M2 macrophage markers were not altered. Also, TIM-3 blockade caused a significant increase in IFN-γ synthesis, which highlights the importance of the use of this immune checkpoint protein in possible future immunotherapeutic approaches [ 73 ].…”
Section: Dendritic Cells and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…13 MDSCs, which are powerful cellular immunity suppressor, could badly inhibit the antitumour immune response mediated by the effector T cells and lead to tumour cells immunological surveillance escape. 28,29 Here, we found that Gal-9 was also highly expressed in MDSCs were much lower than that in real infectious diseases. These suggested that cellular immunity was insufficient for malignant clonal cells due to cellular immunity tolerance, both in low-risk and highrisk MDS groups.…”
Section: Discussionmentioning
confidence: 75%